PENERAPAN FILTER TIKTOK UNTUK PENGENALAN MATA KULIAH DESAIN DAN PENGELOLAAN JARINGAN - Tapola, Yulisa Amny; Koniyo, Moh. Hidayat; Padiku, Indhitya R. (Gorontalo State University, 2024)
This undergraduate thesis aims to apply the TikTok filter in the context of an introduction to Network Design and Management course using the Effect House application with the Face Tracking method. The Face Tracking method is used to follow the users' facial movements, while the Effect House application is used as a platform for applying TikTok filter specifically designed for the purpose of introducing Network Design and Management course. Filter development is done through display design, behavior coding, and filter functionality testing using video samples and facial data. The result of the study shows that applying the TikTok filter in the Effect House application with the Face Tracking method can increase user interaction and involvement. This filter provides an interesting visual experience and makes it easier to access information related to the course. This study contributes to combining the popular elements of social media with educational contexts. Applying the TikTok filter in the Effect House application with the Face Tracking method can be an interesting alternative to enrich the learning experience in the field of Network Design and Management.Keywords: Tiktok Filters; Network Design and Management; Face Tracking